Waldorf Education and Anthroposophy – a Complex Relationship (Global Journal of Human-Social Science, 2023)
Waldorf education Steiner e ducation is one of the most well-established and largest alternative education approaches in the world This educational approach was created out of the Anthroposophical worldview founded by Rudolf Steiner and relies on the teachings of Anthroposophy However the relationship between the educational practice in Waldorf kindergartens and schools and the worldview behind it is complex and multi-faceted both from the internal point of view of those who work from within Waldorf education and from the critical point of view of external researchers Indeed Waldorf education has been criticized and attacked in many ways over the years particularly for these reasons In this article I shall attempt to throw l ight on this connection and explain it from different aspects First I shall briefly present Rudolf Steiner s life path and teachings i e the anthroposophical worldview and then I shall show how Steiner the founder of Waldorf education viewed the connection between Anthroposophy and Waldorf education Subsequently I shall explicate why and how this connection has been subject to criticism from various sides Finally I shall present two ways that try to elucidate this connection and justify it before its critics I shall also endeavor to demonstrate the dangers and challenges that stand before the Waldorf education movement with regard to the fact that it is based on the Anthroposophical worldview
Keywords: waldorf education; rudolf steiner; anthroposophy; steiner education; ideology and education